Public Health Communication Interventions : Values and Ethical Dilemmas. - Guttman, Dr. Nurit (SAGE Publications, 2000)
The ethical dimensions of health communicators' interventions and campaigns are brought into question in this thought-provoking book. Examining the efforts to effect behavior change, the author questions how far health communication can and should go in changing people's values. The author broadens the current analysis of interventions and presents conceptual frameworks that help identify values and justifications that are embedded in health communication goals, strategies, and evaluation criteria. This critical approach helps explain how and why choices are made in design and implementation.